Successful Long-Term Monitoring of Children with Scrofuloderma, Malnutrition, and HIV - Destri Linjani; Finny Fitry Yani (HM Publisher, 2022)
Background: Scrofuloderma is a skin TB that occurs percontinuitatum from tissues underneath, such as lymph nodes, muscles, and bones. It often affects children and young adults. The incidence of TB disease is estimated to increase 20-fold in children with HIV infection. Poor nutrition can affect the mortality rate of children with HIV infection. This case report presents long-term monitoring of boys aged 1 year 5 months with scrofuloderma, malnutrition, and HIV infection. The case report aims to assist children and caregivers in undergoing treatment to prevent drug withdrawal and nutritional procedures and monitor the growth and development of children. Case presentation: A 1-year and 5-month-old boy with a complaint of ulcers on his right neck since 12 months ago. He also complained of diarrhea 12 months ago, accompanied by recurrent stomatitis and progressive weight loss since 3 months ago. He looked pale 1 month ago. Blood laboratory examination with hemoglobin 5.1 gr/dl, leukocytes 5280 / mm3, platelets 323,000 / mm3, hematocrit 20%, reactive anti-HIV test, CD4 examination with a value of 178 cells / L, negative tuberculin test, a chest x-ray showed infiltrate in both lung fields, and bajah examination of the nodules in the Colli dextra region, with the impression of granulomatous inflammation that can be caused by mycobacterial infection. Conclusion: Tuberculosis is the most common opportunistic infection found in children with HIV infection and increases the mortality rate. There is a relationship between nutritional status and the incidence of mortality in HIV/AIDS children, so it is necessary to monitor children for adherence to treatment, improve nutritional status and reduce morbidity and mortality rates.